Decomposição de preços marginais locacionais regida por um modelo completo de compensação distribuída em sistemas de energia elétrica. - SARAIVA, Felipe Oliveira Silva (2021)
Locational marginal prices (LMPs) denote energy monetization benchmarks that are imperative to the deliberations conducted at the core of avant-garde electricity market projects. The implementation of financial hedging instruments to countervail the inherent volatility of LMPs requires the dismemberment of such prices in specific components. Traditional simplified approaches decompose LMPs into three parts: an active energy reference addend, an active power loss addend and a congestion addend. This paper corroborates the existence and the pecuniary relevance of another component of active power LMPs: the reactive power loss component. In the mathematical stratum prior to decomposition, a distributed compensation bus model for spatial allocation of active and reactive power mismatch is incorporated into the optimal power flow (OPF) formulation. The magnitude of the active power LMP components computed through the proposed decomposition approach depends not only on the selection of the active energy reference, but also on the specification of the reactive energy reference. Therefore, the dual nature of the energy reference conceives a legitimate and novel source of litigation among market participants within the scope of financial hedging policies. In the face of the current scenario and future prospects of electric power systems, the market analysis based on the proposed compensation model also considers the effects of the insertion of wind power plants in the power grids. The financial impacts and pertinence of the physicalmathematical framework that governs the proposed LMP decomposition methodology are examined through case studies carried out on the modified IEEE 30-bus test system.